Generalized beam–spring model for predicting elastic behavior of partially composite concrete sandwich wall panels. (1st November 2019) - Al-Rubaye, Salam; Sorensen, Taylor; Thomas, Robert J.; Maguire, Marc
Highlights: No codified analysis methods for partially composite sandwich wall panel elastic behavior exist. A generalized beam-and-spring-based model is shown to provide reasonable accuracy. A parametric study presents plots suitable for preliminary design. Abstract: Partially composite sandwich wall panels (SWP) have been used in the construction industry for at least twenty years. Currently there is limited codified guidance for designers of partially composite concrete SWP, but they are being designed safely and routinely. Design is often guided by the composite connector manufacturers who sell proprietary composite connectors often using a variation of truss-type matrix methods for prediction of elastic behavior of SWPs. The purpose of this paper is to quantify the accuracy of such a model in a uniform manner by developing a generalized version of these matrix models called the beam-spring model (BSM). The primary benefits of the model are its simplicity and versatility making it suitable for design and variations of this model are already in use today. Its accuracy was established in this paper by comparing to 51 specimens from the literature and found to be similar to that of other methods related to strength and cracking of concrete members in the literature. These results indicate that this BSM, or the very similar methods that are already standard practice, provides an adequately safe elastic analysis. On average, the BSM predicted cracking load within 2% with a coefficient of variation (COV) of 7%, out-of-plane panel stiffness within 3% with a COV of 17%, and cracking deflection within 2% with a COV of 18%. These results also indicate that the United States precast industry's use of 7.5 f c ' for predicting the cracking moment is acceptable for partially composite precast panels. A parametric study performed with the BSM presents several different design situations and can be used as a rudimentary design tool for preliminary behavior and arbitrary connectors.